Penyuluhan Hukum terhadap Pencegahan Kekerasan dalam Rumah Tangga di Desa Sidokumpul, Guntur, Demak - Afif Syafiuddin; Uni Sabadina; Marsatana Tartila Tristy (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Community service is one of the main pillars of the Tri Dharma of Higher Education, which plays a strategic role in connecting theoretical knowledge with its real-life application in society. Through these activities, universities not only act as centers for scientific development but also as agents of social change that encourage improvements in the quality of life of the community. This community service article discusses legal counseling activities focused on preventing domestic violence (KDRT), which were carried out in Sidokumpul Village, Guntur District, Demak Regency. This activity aims to increase residents' understanding and legal awareness regarding rights and obligations within the family, as well as providing knowledge about legal procedures that can be taken in the event of domestic violence. The implementation method of the activity included interactive presentations that combined theory with case examples, group discussions to explore problems faced by residents, and the collection and analysis of supporting data regarding the level of legal understanding before and after the activity. This approach allows participants to be actively involved and gain insights relevant to their conditions. The results of the activity show a significant increase in community understanding regarding domestic violence. In addition, an initiative emerged from residents to form a